2008
DOI: 10.1002/jms.1375
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of delta‐9‐THC to delta‐8‐THC when tested as trifluoroacetyl‐, pentafluoropropionyl‐, or heptafluorobutyryl‐ derivatives

Abstract: For GC-MS analysis of delta-9-tetrahydrocannabinol (delta-9-THC), perfluoroacid anhydrides in combination with perfluoroalcohols are commonly used for derivatization. This reagent mixture is preferred because it allows simultaneous derivatization of delta-9-THC and its acid metabolite, 11-nor-delta-9-THC-9-carboxylic acid present in biological samples. When delta-9-THC was derivatized by trifluoroacetic anhydride/hexafluoroisopropanol (TFAA/HFIPOH) and analyzed by GC-MS using full scan mode (50-550 amu), two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Cannabinoids such as THC contain a terpene backbone, and it is not surprising that similar volatile products are generated from dabbing THC, SND, and terpenes alone . A diversity of degradation mechanisms may occur upon thermal treatment of THC, but the significant levels of isoprene seen when dabbing THC alone indicate that the isoprene formed undergoes oxidation to release methacrolein and methyl vinyl ketone, a mechanism for which has been described in the context of atmospheric oxidation. , Isoprene has been previously described as a neutral product formed during fragmentation of THC in electron impact mass spectrometry. The nearly fivefold increase in isoprene released from THC amended with ∼10% terpenes compared to THC alone (Table ) suggests that terpenes release isoprene more readily than THC. Indeed, all identified VOCs form in higher amounts per milligram of product consumed when dabbing SND than from THC alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids such as THC contain a terpene backbone, and it is not surprising that similar volatile products are generated from dabbing THC, SND, and terpenes alone . A diversity of degradation mechanisms may occur upon thermal treatment of THC, but the significant levels of isoprene seen when dabbing THC alone indicate that the isoprene formed undergoes oxidation to release methacrolein and methyl vinyl ketone, a mechanism for which has been described in the context of atmospheric oxidation. , Isoprene has been previously described as a neutral product formed during fragmentation of THC in electron impact mass spectrometry. The nearly fivefold increase in isoprene released from THC amended with ∼10% terpenes compared to THC alone (Table ) suggests that terpenes release isoprene more readily than THC. Indeed, all identified VOCs form in higher amounts per milligram of product consumed when dabbing SND than from THC alone.…”
Section: Discussionmentioning
confidence: 99%
“…CBD conversion to tetrahydrocannabinols by acid catalysis (Figure ) was reported in the literature as early as 1940 by Adams et al, and at least one patent has been issued for this process . The ring-closing reaction to Δ 9 -THC is accompanied by the double-bond isomerization to Δ 8 -THC, which also occurs under acid catalysis, and generation of the latter may be favored by longer reaction times. The use of CBD as a substrate for the synthesis of other cannabinoids has been recently reviewed, and additional products that may result from these processes have been described. , Crude online guides exist for this synthesis, and it has been suggested that some Δ 8 -THC CEC manufacturers do not include a postreaction purification step, potentially resulting in traces of sulfuric acid, hydrochloric acid, trifluoroacetic acid, or p -toluenesulfonic acid .…”
Section: Cannabis E-cigarette Compositionsmentioning
confidence: 99%
“…Cannabinoids. It has been shown that DELTA 9 -THC (9-THC) isomerized to DELTA 8 -THC (8-THC) during derivatization (374). Liquid-liquid or solid-liquid extraction was used to analyze for 9-THC commercial hemp products (375).…”
Section: Drugs and Poisonsmentioning
confidence: 99%